1988
DOI: 10.1016/0006-291x(88)90675-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and kinetic characterization of nitric oxide and EDRF released from cultured endothelial cells

Abstract: Endothelial cells (EC) contribute to the control of local vascular diameter by formation of an endothelium derived relaxant factor (EDRF) (1). Whether nitric oxide (NO) is identical with (EDRF) or might represent only one species of several EDRFs has not been decided as yet (2-5). Therefore, we have directly compared in cultured EC the kinetics of NO formation determined in a photometric assay with the vasodilatory effect of EDRF and NO in a bioassay. Basal release of NO was 16, 4 pmol/min/ml packed EC column.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
107
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 336 publications
(116 citation statements)
references
References 15 publications
9
107
0
Order By: Relevance
“…70Mm diameter can be adequately resolved (Griffith et al, 1988). Haemoglobin appears to be a specific inhibitor of EDRF activity at the concentration employed (1 gM) (Martin et al, 1985;Edwards et al, 1986;Kelm et al, 1988;Nishiye et al, 1989 (Cocks & Angus, 1983;Miller & Vanhoutte, 1985;Egleme et al, 1984;Matsuda et al, 1985), there is no evidence that al-adrenoceptors can do so in any species or artery type. The lack of effect of haemoglobin in the absence of a constrictor agonist in this preparation differs from previous experiments with the rabbit isolated ear, in which inhibition of basal EDRF activity induced a small but significant rise in perfusion pressure in the absence of exogeneous constrictor agents and in which haemoglobin therefore unmasked myogenic tone (Griffith et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…70Mm diameter can be adequately resolved (Griffith et al, 1988). Haemoglobin appears to be a specific inhibitor of EDRF activity at the concentration employed (1 gM) (Martin et al, 1985;Edwards et al, 1986;Kelm et al, 1988;Nishiye et al, 1989 (Cocks & Angus, 1983;Miller & Vanhoutte, 1985;Egleme et al, 1984;Matsuda et al, 1985), there is no evidence that al-adrenoceptors can do so in any species or artery type. The lack of effect of haemoglobin in the absence of a constrictor agonist in this preparation differs from previous experiments with the rabbit isolated ear, in which inhibition of basal EDRF activity induced a small but significant rise in perfusion pressure in the absence of exogeneous constrictor agents and in which haemoglobin therefore unmasked myogenic tone (Griffith et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The endothelium-dependent relaxation of arterial Zawadski, 1980;Griffith et al, 1984), identical with smooth muscle which can be induced by a wide or closely related to nitric oxide (Ignarro et al, 1987; variety of compounds such as acetylcholine (ACh), is Palmer et al, 1987;Furchgott, 1988), and is avidly mediated by stimulated release of endotheliumbound by haemoglobin (Kelm et al, 1988). derived relaxing factor (EDRF).…”
Section: Introductionmentioning
confidence: 99%
“…The NO generation rate was calculated from the change in the absorption at 401 nm minus 411 nm as a function of time (ε 401-411 = 38 mM -1 cm -1 ) [36]. The assay mixture consisted of the control or oxidant exposed nNOS in 50 mM Tris-HCl, pH 7.4, as described above, with 200 μM CaCl 2 , 10 μg/ml CaM, 150 μM DTT, 200 μM NADPH and 10 μM oxyhemoglobin added.…”
Section: Oxyhemoglobin Assay Of No Generation Ratementioning
confidence: 99%
“…In biological systems, it is produced in very low concentrations, and it has a very short half-life (< 6 s) (2). Under physiological conditions, NO may degrade to nitrite (NOi~) and also nitrate (NOJ").…”
Section: Introductionmentioning
confidence: 99%
“…Funding Organization: The National Heart, Lung and Blood Institute, 9000 Rockville Pike, Bethesda, MD 20892, U.S.A. 2 ) Enzyme: Nitric oxide synthase reduction and Griess reagent reaction. We found that the samples always produced more colour or apparent NOJ in the presence than in the absence of nitro-Z,-arginine.…”
Section: Introductionmentioning
confidence: 99%